Relationship of knowledge and attitude with food handling practices: A systematic review - Kholis Ernawati; Qatrunnada Nadhifah; Anis Muslikha; Muhammad Hidayat; Tri Edhi Budhi Soesilo; Fathul Jannah; Dini Widianti; Yusnita Yusnita (Intelektual Pustaka Media Utama, 2021)
Foodborne disease is still a public health problem in several countries. Food handler's knowledge, attitude, and practice (KAP) are factors that are risk factors for foodborne disease incidence. The research objective was to assess the level of knowledge, attitudes, and behavior of food handlers in maintaining food hygiene using a systematic review approach. The research method used is the preferred reporting items for systematic review and meta-analyses (PRISMA) protocol approach. The article search process was accessed on PLOS ONE, Pro-Quest, and Google Scholar. A descriptive analysis was carried out on each research variable. The results obtained eight papers (100% sociodemography, 100% knowledge, 62.5% attitude, and 87.5% behavior). The mean of significant articles on sociodemographic variables was 18.5%, experience 59.38%, attitudes 13.33%, and 23.81%. There are 37.5% of the articles showed significant relationship between knowledge and attitude with food handling practice.